ENSURING THE LEGAL SAFEGUARDING OF FOREIGN INVESTMENTS IN INDONESIA'S MINERAL AND COAL MINING SECTOR - Fadhilah, Dening Putri; Saputri, Atha Difa (Universitas Negeri Semarang, 2024)
Foreign investment in Indonesia's mineral and coal mining sector necessitates robust legal protection mechanisms. This paper explores the complexities surrounding legal frameworks and regulations governing foreign investment, aiming to ensure investor security and safeguarding. Methodologically, it examines relevant Indonesian laws, including Law Number 25 of 2007 and Law Number 3 of 2020, concerning Capital Investment and Mineral and Coal Mining, respectively. Results reveal ongoing challenges, including authority conflicts and licensing processes, hindering optimal sectoral contributions to national economic growth. Nonetheless, opportunities for foreign investment persist, particularly through work contract agreements. Adherence to Indonesian legal requirements, collaboration with local entities, and compliance with ownership structures and investment amounts are imperative for foreign investors. The paper underscores the government's commitment to enforcing compliance through administrative and criminal sanctions, promoting domestic participation in the sector. Overall, continual evaluation and adaptation of regulations are vital to ensuring sustainable and mutually beneficial foreign investment in Indonesia's mineral and coal mining sector. KEYWORDS Foreign investment, legal protection, mineral and coal mining, Indonesia.